THE IMPACT OF GOODS PRODUCT PRICING STRATEGIES ON CONSUMER PURCHASING POWER: A REVIEW OF THE LITERATURE - Pandu Adi Cakranegara; Wandi Kurniadi; Ferdinandus Sampe; Jouri Pangemanan; Muhammad Yusuf (SEAN Institute, 2022)
The price of a product is a measure of the exchange rate used to obtain it in the form of money or goods. In order to achieve the desired business goal and profit, a company must exercise caution when determining the price of a product, service, or good. Pricing must take into account a variety of factors, as well as the best strategy. In this way, the set price can pique consumer interest and influence consumer purchasing power. The purpose of this research is to determine how the company's pricing affects consumers' purchasing power or purchasing interest. This study employed a qualitative approach in the form of literature reviews in the field of marketing management. Writing scientific articles necessitates the use of qualitative methods as well as literature studies or library research. The price of a company's product or service has a positive effect on consumer purchasing interest, so it is closely related to consumer purchasing power. Consumers' increased purchasing power at company-set prices has an impact on meeting company targets and increasing profits.